Tumour necrosis factor plays a deleterious role in the pathogenesis of chikungunya virus infection. Issue 3 (14th November 2022) - Moreira, Thaiane Pinto; Sousa, Carla Daiane Ferreira de; Melo Costa, Victor Rodrigues de; Queiroz‐Junior, Celso Martins; Santos, Franciele Martins; Bonilha, Caio Santos; Ésper, Lísia Maria; Nogueira, Mauricio Lacerda; Cunha, Thiago Mattar; Teixeira, Mauro Martins; Costa, Vivian Vasconcelos; de Souza, Daniele da Glória
Abstract: Arthralgia is a hallmark of chikungunya virus (CHIKV) infection and can be very debilitating and associated with a robust local inflammatory response. Many pathophysiological aspects associated with the disease remain to be elucidated. Here, we describe a novel model of CHIKV infection in immunocompetent mice and evaluate the role of tumour necrosis factor in the pathogenesis of the disease. C57BL/6 wild type (WT) or TNF receptor 1 deficient (TNFR1 −/− ) mice were inoculated with 1 × 10 6 PFU of CHIKV in the paw. Alternatively, etanercept was used to inhibit TNF in infected WT mice. Hypernociception, inflammatory and virological analysis were performed. Inoculation of CHIKV into WT mice induced persistent hypernociception. There was significant viral replication in target organs and local production of inflammatory mediators in early time‐points after infection. CHIKV infection was associated with specific humoral IgM and IgG responses. In TNFR1 −/− mice, there was a decrease in the hypernociception threshold, which was associated with a milder local inflammatory response in the paw but delayed viral clearance. Local or systemic treatment with etanercept reduced CHIKV‐induced hypernociception. This is the first study to describe hypernociception, a clinical correlation of arthralgia, in immunocompetent mice infected with CHIKV. It also demonstrates the dual role of TNF in contributing to viral clearance but driving tissue damage and hypernociception. Inhibition of TNF may have therapeutic benefits but its role in viral clearance suggests that viral levels must be monitored in CHIKV‐infected patients and that TNF inhibitors should ideally be used in combination with anti‐viral drugs. Abstract : Absence of TNF receptor is associated with an improvement in clinical and inflammatory parameters of CHIKV infection.